Atmospheric electricity as a proxy for air quality: Relationship between potential gradient and pollutant gases in an urban environment - Silva, Hugo (2016)
A relationship between Trace Gases (TG), NOx, SO2, O3, and the Atmospheric Electric Potential Gradient (PG), through Ion/Particulate Matter (PM) interaction, is established in the urban environment of the city of Lisbon (Portugal). Analysis was restricted to 1988–1990, when simultaneous measurements of PG and TG were taken. Reasonable linear relationships between PG and TG concentrations have been found. A formulation relating PG with TG concentrations allows the estimation of constants of proportionally between TG-PM to be ∼50 cm−3 ppb−1; which are similar to the values found in direct TG-PM measurements in UK cities, validating the present results.